The Discourse of Corruption in Mass Media: Polarization, Ideology, and Challenges - Anang Sujoko; Dicky Wahyudi; Muzakky Abdillah (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
This article presents the opposing point of view between Tempo Newspaper and Media Indonesia in reporting on the revision of the KPK Law after the presidential inauguration. The analysis focuses on the ideology reconstruction of both of those media. The method uses critical discourse analysis to uncover the invisible power, interests, and ideology behind the contents and elements of the articles and the production of a text on Tempo Newspaper and Media Indonesia. The ﬁndings that Media Indonesia's ideology in reporting the revision of the KPK Law is based on the political interests of the media owners, thus in this case, Media Indonesia considers the revision of the KPK Law as an effort to improve and strengthen the performance of the KPK with a pro-government narrative. Meanwhile, Tempo's ideology in reporting the revision of the KPK Law was based on elite interests, so the ideology used was investigative ideology by building a criticizing narrative based on the facts found. This study aims to increase public awareness of the importance of critically viewing this polarization; thus, the harmful excesses of political propaganda do not easily provoke them through mass media.